2015
DOI: 10.1186/s12957-015-0668-5
|View full text |Cite
|
Sign up to set email alerts
|

Localized primary gastrointestinal diffuse large B cell lymphoma received a surgical approach: an analysis of prognostic factors and comparison of staging systems in 101 patients from a single institution

Abstract: BackgroundDiffuse large B cell lymphoma (DLBCL) represents the most common histological subtype of primary gastrointestinal lymphoma and is a heterogeneous group of disease. Prognostic characterization of individual patients is an essential prerequisite for a proper risk-based therapeutic choice.MethodsClinical and pathological prognostic factors were identified, and predictive value of four previously described prognostic systems were assessed in 101 primary gastrointestinal DLBCL (PG-DLBCL) patients with loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…Notably, studies from Wang et al (42) and Dai et al (43) reported that in early-stage ENKTCL, B symptoms, including fever, weight loss and night sweats, are not associated with prognosis. The results from the present study were consistent with those from these previous studies (41,42), and were also similar to those from studies on some early-stage lymphomas (44,45).…”
Section: Discussionsupporting
confidence: 93%
“…Notably, studies from Wang et al (42) and Dai et al (43) reported that in early-stage ENKTCL, B symptoms, including fever, weight loss and night sweats, are not associated with prognosis. The results from the present study were consistent with those from these previous studies (41,42), and were also similar to those from studies on some early-stage lymphomas (44,45).…”
Section: Discussionsupporting
confidence: 93%
“…Endoscopic examination combined with pathological biopsy is still the most important and reliable method for detection of PGI-DLBCL. Nowadays, there is still no consensus on its treatment, the majority of patients were treated with combined therapy (chemotherapy and radiotherapy, surgery plus chemotherapy, surgery plus chemotherapy, and radiotherapy).The majority of chemotherapeutic protocols was CHOP (cyclophosphamide, doxorubicin, vincristine, prednisolone)-like regimens and/without rituximab [4][5][6]. Immunodeficiency is considered to be one of the most dangerous factors in NHL, with a greater risk of developing lymphoma with congenital or acquired immunodeficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We identified the histologic subtype of iL as a relevant but nonsignificant factor associated with lymphoma-specific survival, observing more patients with aggressive histologic subtype who died of disease [17,18].…”
Section: Discussionmentioning
confidence: 99%